CONTROVERSY AND CONFLICTS DUE TO IMPROPER MEDICAL CARE AND LEGAL PRACTICE OF THEIR RESOLVING - I. O. Perepechina; D. V. Perepechin; D. V. Smirnova (Исследования и практика в медицине)
The paper presents the analysis of the statistical data on the Russian Federation, showing how often controversy and conflicts due to improper medical care occurs in medical practice, as well as what are the ways to resolve them.